Problem Base Learning Virtually In Blended Learning Model for Chemistry Lessons During The Covid-19 Pandemic - Nurin fitriana; Febi Dwi Widayanti; Bayu Firmanto (JURNAL PENDIDIKAN SAINS UNIVERSITAS MUHAMMADIYAH SEMARANG, 2021)
Learning from home become one of the government's policies in overcoming the Covid-19 pandemic that hit Indonesia and even the world today. This becomes the foundation of learning activities that require to use of internet technology so that learning objectives continue to run and are achieved. The use of online learning must be well planned so that students can still be student-centered who can construct their knowledge with contextual abilities. Problem Base Learning Virtually (PBL-V) is one model that can be implemented in exploring student understanding. This type of research is quantitative descriptive with data collection techniques through a questionnaire using a Likert scale. The results of this assessment indicate a positive response strongly agreed as much as 53% of the use of PBL-V in the learning activities of the chemistry lessons. As many as 63% of students expressed strongly agree with the use of blended learning composition offline: online 10:90. Offline is carried out before the social restriction regulations are then carried out online learning so that learning objectives are still achieved during the Covid-19 pandemic.